Faktor-Faktor Yang Memengaruhi Penentuan Jumlah Anak Dalam Keluarga Di Kecamatan Bukit Kabupaten Bener Meriah: Faktor-Faktor Yang Memengaruhi Penentuan Jumlah Anak Dalam Keluarga Di Kecamatan Bukit Kabupaten Bener Meriah - Nurlaely HS; Rahma Yani (Jurnal Ilmiah Cerebral Medika, 2021)
ABSTRACT Indonesia is one country that has many population problems that until now can not be overcome. The government has devised a policy to control the rate of population growth. Control is an attempt or activity to limit population growth, by reducing the number of births. Population policy is known as Family Planning (KB) program. This study aims to determine the effect of factors on the determination of the number of children in the family in Bukit District Bener Meriah regency. This research type is analytic survey with cross sectional approach. This study was conducted from January 2020. The population of this study was 13,618 people. The number of samples in this study as many as 99 people. Multivariate data analysis using logistic regression test. The result showed that family support factor, socio-cultural / belief, economy, child value and contraceptive use were related to the determination of the number of children in the family and socio-cultural variables is the most dominant variable affecting the determination of the number of children in the family with the value of Exp (B) 23.009 (CI: 95%, 5,193-101,935). The conclusions of this study are socio-cultural factors in couples of childbearing age that do not support 23,009 times greater to have a large number of children in the family compared with supportive socio-cultures. It is expected that health workers at Bukit sub-district health center can improve the quality of service especially about health promotion service or counseling about healthy family and quality according to family planning program which proclaimed by the government through media of counseling to both couples of childbearing age and health officer by involving religious leaders and public figures in villages that became the working area of Puskesmas in Bukit sub-district. Keywords : Family Support, Socio-Culture Trust, Economy